2010
DOI: 10.1002/ajh.21824
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lymphoid neoplasms in the Republic of Korea: Analysis of 5318 cases according to the World Health Organization classification

Abstract: Compared with the West, the overall incidence of lymphoid neoplasms is lower, and the subtype distribution is distinct in Asia. To comprehensively investigate the subtype distribution with the age and sex factors, and temporal changes of subtype proportions, we re-assessed all patients with lymphoid neoplasms diagnosed at a large oncology service in the Republic of Korea from 1989 to 2008 using the World Health Organization classifications. Of the total 5,318 patients, 66.9% had mature B-cell neoplasms, 12.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
123
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 41 publications
22
123
8
1
Order By: Relevance
“…Follicular lymphomas (FL) represent nearly 20% of all NHL in our study. This is a relatively high percentage when compared to the FL percentage in China (9%) (Yang et al, 2011), Korea (3%) (Yoon et al, 2010) and US (10%) (Wu et al, 2009), where FL represents less than 10% of all NHL. Similarly a high proportion of FL is described in the French population (20%) (Troussard et al, 2009) (Table 2).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Follicular lymphomas (FL) represent nearly 20% of all NHL in our study. This is a relatively high percentage when compared to the FL percentage in China (9%) (Yang et al, 2011), Korea (3%) (Yoon et al, 2010) and US (10%) (Wu et al, 2009), where FL represents less than 10% of all NHL. Similarly a high proportion of FL is described in the French population (20%) (Troussard et al, 2009) (Table 2).…”
Section: Resultsmentioning
confidence: 85%
“…In Asia, HL incidence doesn't exceed the 5% in Korea (Yoon et al, 2010) and in China 13% (Yang et al, 2011). In developed countries, HL represents 9% of all lymphoma cases in the US (Morton et al, 2006), 13% in England (Lowry and Linch, 2013) and 16% in France (Troussard et al, 2009).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous pioneer study from North India has shown the incidence to be 44% (106 of 241 cases of NHLs over a 3 year period) (Singh et al, 2003). However, the incidence of pENL has been shown to be very high in neighbouring Pakistan and Saudi Arabia (up to 50%) (Nagi et al, 2011), Kuwait (45%) (Temmim et al, 2004), Northern Iraq (48.3%) (Yaqo et al, 2011), Taiwan (47.2%) (Chen et al, 2010), Japan (46.6%) (Fujita et al, 2009), Korea (55%) (Yoon et al, 2010), Thailand (58.7%), and China (44.9%-61.4%) (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…), skin, central nervous system (CNS), bone, testis, thyroid, breast, orbit, and rarely adrenal, pancreas, and the genitourinary tract (Singh et al, 2003;Temmim et al, 2004;Al Shemmari et al, 2008;Aoki et al, 2008;Gross et al, 2008;Lal et al, 2008;Fujita et al, 2009;Chen et al, 2010;Yoon et al, 2010;Yun et al, 2010;Arora et al, 2011;Nagi et al, 2011;Yaqo et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%